Does Spousal Support Can Increase the Women's Physical Activity? - Hajar Rezaee; Maryam Amidi Mazaheri (Shiraz University of Medical Sciences, 2017)
Background: Numerous benefits of physical activity are well-known for the prevention and treatment of various diseases such as diabetes, cardiovascular disease, obesity, and cancers. However, the status of physical activities among women remains noticeably less than the recommended level. Considering the importance of the spouses' participation in the promotion of women's health, this study examined the impact of spousal support on women's physical activity. Methods: This semi--experimental study was done in February 2015 on 100 couples in reproductive age referred to health centers of Falavarjan city. The participants were randomly divided into intervention and control groups. The information related to women's physical activity in both groups was collected by aquestionnaire in two steps, before and three months after the intervention. The spouses of women in the intervention group were trained in the field of the importance of physical activity in women's health in two sessions. The data were analyzed by the software SPSS21 and suitable statistical tests (Independent t, paired t, and Chi-square). Results: The mean and standard deviation of women's age in the both groups were 28.76±5.51 and 30.38±5.31, respectively. The prevalence of obesity and overweight in the women under the study was generally estimated 44%. Physical activities of women in the intervention group were significantly increased after the intervention (P<0.0001). Also, the Body Mass Index in the intervention group was significantly decreased compared to before the intervention and control group (P<0.001). Conclusion: Spouses could encourage women to perform physical activities. It is recommended that the health care system should implement educational sessions for men to encourage women to exercise.